Working brief ([CCS] [Georgetown]GY, 2004)
Deals with the law, ethics and human rights. Looks at stigma and discrimination in the prevention and control of the HIV/AIDS epidemic. Focuses on ethical issues and human rights principles for HIV/AIDS epidemiology.
Keywords: HIV